Analysis of inspection system based on zero acceptance plans with inspection errors - Chattinnawat,W. (Chiang Mai University, 2015)
This research evaluate the impact of inspection errors on Zero sampling Plans conducted at incoming, outgoing quality assurance and at Customer site. The incoming lot size is largely greater than the production lot size. With inspection errors of Type II presented, the lot acceptance rate at producer site is increased as expected whereas that at customer site is decreased. The relationship between the amount of inspection errors and the lot acceptance rate can help producer estimate the current inspection error at both incoming and outgoing quality station which will lead to improvement project plans.